Knowledge, Health Beliefs, and Self-Efficacy regarding Osteoporosis in Perimenopausal Women - Renée D. Endicott (Journal of Osteoporosis)
The aims of this pilot study were to (1) determine if having a family history of osteoporosis impacts knowledge, health beliefs, and self-efficacy regarding osteoporosis among perimenopausal women aged 42–52 and to (2) describe the impact of an osteoporosis-specific educational intervention had on the knowledge, health beliefs, and self-efficacy of this population. Participants completed three surveys measuring knowledge, health beliefs, and self-efficacy related to osteoporosis before and two months after the educational program. At baseline, no differences were noted in knowledge of osteoporosis among women with and without a family history of osteoporosis, although women with a family history perceived a greater susceptibility for developing osteoporosis than women without the family history. Findings indicate that both groups increased in knowledge of osteoporosis (P<.001). Benefits of calcium increased in the women without a family history of osteoporosis (P<.001) and benefits of exercise increase in women with a family history of osteoporosis (P=.007). There were no significant statistical findings regarding self-efficacy between the two groups of women. Findings indicate that an osteoporosis-specific educational program improves perimenopausal women’s knowledge and some health beliefs.